Antyproliferacyjny wpływ kwasu mykofenolowego na komórki nabłonka barwnikowego siatkówki in vitro - Kaczmarek, Radosław; Zaczyńska, Ewa; Misiuk-Hojło, Marta (Klinika Oczna / Acta Ophthalmologica Polonica, 2010)
Purpose: Mycophenolate mofetil (MMF) is an immunosuppressive agent used in the prophylaxis of graft rejection in transplantology. Its antyproliferative effects on lymphocyte, monocytes, vascular smooth muscle cells and fibroblasts are well known, but to our knowledge there are no reports on its action on the retinal epithelial (RPE) cells in vitro. Material and methods: In all experiments we used mycophenolic acid (MPC), which is the biologically active form of MMF. Its activity was assessed on the cultures of immortalized non-transformed cells line from a human donor (ARPE19). Cells were seeded and incubated in vitro with deferent concentrations of MPC: 0.0025 µg/ml, 0.025 µg/ml, 0.25 µg/ml, 2.5 µg/ml, 25 µg/ml and 250 µg/ml. After 24 and 72 hours of incubation, proliferative activity was assessed by 5’-bromo-2’-deoxyuridine (BrdU) incorporation into cellular DNA and the amount of cell proliferation was determined using the 3-(4.5-dimethylthiazol-2yl)-2.5- -diphenyltetrazolium bromide (MTT) assay. Additionally, to determine cytotoxicity of MPC, ARPE19 cells were grown to confluence and subsequently cultured in a serum-deficient medium and then, after 24 hours of incubation with diferent concentrations of MPC, the MTT test was performed. Results: The BrdU assay showed the decrease of DNA synthesis activity for increasing concentrations of MPC starting with 0.025 µg/ml to 250 µg/ml. The number of RPE cells assessed with MTT test decreased after the exposition to the drug concentrations of 25 µg/ml and 250 µg/ml after 24 and 72 hours of incubation, and additionally for the concncentrations of 0.25 µg/ml and 2.5 µg/ml after 72 hours of incubation. Conclusions: MMF influences the proliferation of immortalized ARPE19 cells without evident cytotoxic effect.